2007
DOI: 10.1074/jbc.m704329200
|View full text |Cite
|
Sign up to set email alerts
|

High Titers of Transmissible Spongiform Encephalopathy Infectivity Associated with Extremely Low Levels of PrPSc in Vivo

Abstract: Diagnosis of transmissible spongiform encephalopathy (TSE) disease in humans and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
111
0
3

Year Published

2008
2008
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 150 publications
(120 citation statements)
references
References 42 publications
6
111
0
3
Order By: Relevance
“…Other recent in vitro experiments support the concept that different PrP conversion pathways can result in differences in both infectivity and in vitro amyloid formation (39). Further evidence for extensive variation in the quantitative correlation between PrPres and infectivity in brain has also been noted previously by others (40,41). Together all these findings support the conclusion that measurement of PrPres from PMCA or in vivo tissue sources is not a reliable quantitative marker for prion infectivity.…”
Section: Discussionsupporting
confidence: 77%
“…Other recent in vitro experiments support the concept that different PrP conversion pathways can result in differences in both infectivity and in vitro amyloid formation (39). Further evidence for extensive variation in the quantitative correlation between PrPres and infectivity in brain has also been noted previously by others (40,41). Together all these findings support the conclusion that measurement of PrPres from PMCA or in vivo tissue sources is not a reliable quantitative marker for prion infectivity.…”
Section: Discussionsupporting
confidence: 77%
“…It is nevertheless possible that limited muscle sampling and methodological insensitivity could fail to detect the irregular distribution of low levels of PrP TSE in muscle. Moreover, the absence of PrP TSE does not necessarily imply absence of infectivity (Barron et al, 2007;Berardi et al, 2006;LasmĂ©zas et al, 1997). A more thorough examination of entire muscle groups using the ultrasensitive proteinmisfolding cyclic-amplification technique (Soto et al, 2005) might yield a positive result, but would need to be verified by infectivity bioassay before inferring a risk of disease transmission.…”
mentioning
confidence: 99%
“…18,19 In particular, Barron and coworkers demonstrated that tissues with very low levels of PK-resistant PrP Sc could be highly infective. 20 In this regard, the expression of scFvD18 could have hampered the formation of PK-resistant PrP Sc without interfering with an alternative PK-sensitive PrP Sc isoform.…”
Section: Distribution Of Aav9 In the Cnsmentioning
confidence: 99%